Dosimetric uncertainties impact on cell survival curve with low energy proton. (August 2020) - Tan, Hong Qi; Koh, Wei Yang Calvin; Yeo, Eugenia Li Ling; Ang, Khong Wei; Poon, Dennis Jun Jie; Lim, Chu Pek; Vajandar, Saumitra K.; Chen, Ce-Belle; Ren, Minqin; Osipowicz, Thomas; Soo, Khee Chee; Chua, Melvin Lee Kiang; et al.
Highlights: Microdosimetric spectra is important for low energy proton through thin target. Broad microdosimetric spectra introduces dosimetric uncertainty in the cell. Dose estimation with average stopping power in cell improves reproducibility. Both random and systematic error can be introduced in the cell survival curve. Alpha and Beta uncertainties can be up to 10% and above 30% respectively. Abstract : Abstract: There is an increasing number of radiobiological experiments being conducted with low energy protons (less than 5 MeV) for radiobiological studies due to availability of sub-millimetre focused beam. However, low energy proton has broad microdosimetric spectra which can introduce dosimetric uncertainty. In this work, we quantify the impact of this dosimetric uncertainties on the cell survival curve and how it affects the estimation of the alpha and beta parameters in the LQ formalism. Monte Carlo simulation is used to generate the microdosimetric spectra in a micrometer-sized water sphere under proton irradiation. This is modelled using radiobiological experiment set-up at the Centre of Ion Beam Application (CIBA) in National University of Singapore. Our results show that the microdosimetric spectra can introduce both systematic and random shifts in dose and cell survival; this effect is most pronounced with low energy protons. The alpha and beta uncertainties can be up to 10% and above 30%, respectively for low energy protons passing through thin cell target (about 10 microns). These uncertainties are non-negligible and show that care must be taken in using the cell survival curve and its derived parameters for radiobiological models.